'Kalakarm Curriculum': How can illustration facilitate art in education?. Issue 1 (6th April 2023) - Gupta, Siddhi
This article elucidates the journey of the author as an illustrator and educator in the Indian art education landscape, pivoted around the case study of the project called 'Kalakarm Curriculum'. The author enquires how these roles guide her decisions to develop a distributable resource that can make art education possible in the classroom. A vital part of the process is the primary research conducted at government and low-income private schools in Delhi, India, which provides the necessary constraints to limit the scope of the large issue of art education in India into a workable brief. The project is anchored around the aspirations and challenges of educators who teach different subjects to different age groups, mapped through conversations, observations and the method of workshops. Illustration is used to document the project, communicate its intention, as a process to make meaning and to create the resource that can equip educators to be able to achieve art in education. The end of the project is education – a particular imagination of art education – to make it accessible and transferrable first from the author to the educators and then from the educator to the learners.